Analysis of the influence of Work Culture on Job Satisfaction of STMIK Pelita Nusantara Employees - Edro William Purba (SEAN Institute, 2022)
Satisfaction in work will affect productivity which is expected by the leadership of STMIK Pelita Nusantara. For that, institutional leaders need to understand what must be done to create employee job satisfaction. STMIK Pelita Nusantara is engaged in education. From a preliminary study conducted at STMIK Pelita Nusantara, it shows that most employees generally feel dissatisfied with their work. This is shown from the attitude and behavior of employees at work, for example, the frequent absences of employees from work, often procrastinating on work that should be completed immediately, and more conversations among colleagues at work. The formulation of the problems in this study are: 1) How is the influence of work culture and incentives on job satisfaction of employees at STMIK Pelita Nusantara, 2) What factors influence the incentives for employees at STMIK Pelita Nusantara? While the hypotheses put forward in the study are: 1) Work culture and incentives have an effect on employee job satisfaction at STMIK Pelita Nusantara, 2) Company ability and willingness, work productivity, position positions, and education and work experience affect the incentives for employees in STMIK Pelita Nusantara.